Doing Business in Egypt 2008 - World Bank (World Bank, Washington, DC, 2016)
Doing Business in Egypt 2008 covers three topics at the sub national level: starting a business, dealing with licenses and registering property. These indicators have been selected because they cover areas of local jurisdiction and practice. In the last two years, doing business in Egypt has become more affordable the minimum capital required to start a business and the costs of registering property and dealing with licenses have been slashed. Doing Business in Egypt 2008 records all procedures required for a business in the construction industry to build a standardized warehouse. Doing Business in Egypt 2008 records the full sequence of procedures necessary when a business purchases land and a building to transfer the property title from another business so that the buyer can use the property for expanding its business, as collateral in taking new loans or, if necessary, to sell to another business. The ease of doing business index is limited in scope. The Doing Business indicators provide a new empirical data set that may improve understanding of these issues.